PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, KOMPETENSI SUMBER DAYA MANUSIA, SISTEM AKUNTANSI KEUANGAN DERAH DAN PENGAWASAN FUNGSIONAL TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kota Pariaman) - Lopita Turwirdani; Restu Agusti; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of thegovernment internal controlsystem, the competence human resources, financial accounting systems area, and functional supervision on effectiveness of financial management area.The research was conducted on the regional work units ofPariaman.This study used purposive sampling method. The sample in this study is the Head of SKPD, Secretary of SKPD, Head of Sub Division of Finance, and Chief Financial administrator. The sample used in this study were 76 respondents. The statistical method used to test the hypothesis of the research is multiple linear regression analysis using SPSS.The results showed that the variables ofthegovernment internal controlsystem, the competence of human resources, financial accounting systems area, and functional supervision influence on effectiveness of financial management area pariaman city.Keywords:Internal control, competence, financial accounting, and supervision, effectiveness.